3D Printing of Carbides Using Renewable Resources. (5th April 2018) - Carrillo, Gabriel; Sullivan, Morgan Claire; Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : Here we present our initial results for fabrication of 3D cellular architectures of tungsten carbide by 3D printing. We 3D printed cellular architectures of a biopolymer gel composite that consisted of iota-carrageenan and chitin as carbon precursors and tungsten tri-oxide as the tungsten source. The 3D printed gel composite was dried to obtain a 3D structure of biopolymer xerogel. Heat treatment of the xerogel structures resulted in 3D cellular architectures of porous tungsten carbide (WC). Significant shrinkage occurred during the drying and heat treatment process. The X-ray diffraction pattern confirmed that WC was formed after heat treatment. Scanning electron microscopy showed that the WC formed here featured a porous network of particle agglomerates. Ongoing work includes compressive testing to determine the Young's modulus of samples. A design of experiments will be implemented to develop a relationship between mechanical behavior and the geometry of the cellular architecture. Additionally, shrinkage, material solvent, printing substrate and filament diameter require further study to control rheology and increase precision during fabrication.